(untitled) (KYAMC Journal, 2013)
Mrs. Lalbanu 65 years old lady presented to us with the complaints of something coming down per vagina for 10 years, foul smelling discharge for 2 months, fever & maggot formation for 5 days, she also gave history of applying some chemical substances on her prolapsed mass of genitalia, and she also complains of lower abdominal pain for last 5 days. On examination, prolapsed mass was distorted, edematous, infected, irreducible & there were maggots, her temperature was raised & having lower abdominal tenderness. She was treated at first conservatively & then surgically. Now she is well & with our follow up. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13662 KYAMC Journal Vol. 3, No.-1, June 2012 pp.262-264